Comparative Evaluation of Cytokinin-Induced In Vitro Shoot Multiplication in Black Ginger (Kaempferia paviflora Wall. ex Baker) - Tambunan, Muhammad Iqbal H.; Tarigan, Lola Zeramenda Br; Saragih, Sisca Sri Dewi; Ritonga, Hayati Sakinah (Program Studi Pendidikan Biologi, 2025)
Kaempferia parviflora Wall. ex Baker (Zingiberaceae), commonly known as black ginger, produces dark purple to black rhizomes rich in bioactive compounds. Conventional propagation of K. parviflora is constrained by limited planting material availability. This study evaluated the effectiveness of various cytokinins for in vitro shoot multiplication of K. parviflora. Nodal explants derived from sterile in vitro stock were cultured on Murashige & Skoog medium supplemented with one of seven treatments: P₀ (no cytokinin), P₁ (1 mg L⁻¹ BAP), P₂ (2 mg L⁻¹ BAP), P₃ (1 mg L⁻¹ kinetin), P₄ (2 mg L⁻¹ kinetin), P₅ (1 mg L⁻¹ TDZ), or P₆ (2 mg L⁻¹ TDZ), with ten replicates per treatment. Parameters recorded after eight weeks included explant survival percentage, shoot number, leaf number, and shoot length. Explant survival averaged 94 % across treatments. Treatment P₆ (2 mg L⁻¹ TDZ) yielded the highest mean shoot number (4.9 ± 2.6 shoots) and leaf number (9.3 ± 2.2 leaves) per explant. The superior performance of low‑concentration TDZ compared to BAP and kinetin shows its high efficacy in promoting cytokinin‑mediated shoot proliferation.